Habitat distribution modeling of the Pinus gerardiana under projected climate change in the North-Western Himalaya, India - Paul, Shiv; Lata, Swaran; Barman, Tanay (Landscape and ecological engineering, 2023)
Pinus gerardiana Wall. ex D. Don (Champion of the Rocky Mountains) is found in the dry temperate forests of Tibet, India, Afghanistan, and Baluchistan—Pakistan. It produces delicious and extremely nutrient-rich nuts or kernels. In the Western Himalaya, the seeds of the species are highly valued for their many cultural and medicinal value. Due to conversion of Chilgoza pine forest to agricultural land, excessive seed cone harvesting, overgrazing and overexploitation for firewood population of the species is quickly declining. Hence, the study was conducted in Himachal Pradesh, North-Western Himalaya to identify suitable areas for the occurrence of the species under projected climate change. To predict the potential suitability model of P. gerardiana , species occurrence data, bioclimatic variables, and the MaxEnt modeling approach were used. The model calibration test for P. gerardiana has AUC test = 0.978 ± 0.067 and TSS value 0.917 ± 0.188 and falls under the good level of accuracy. The model’s results indicated that 1070 km 2 (1.92%) geographical area of Himachal Pradesh is suitable for the existence of P. gerardiana . The current work used the CMIP6 (Coupled Model Intercomparison Project Phase 6) project’s BCC-CSM2-MR, IPSL-CM6A-LR and MIROC6 climate change models to predict the probability distribution model of P. gerardiana under the SSP245 (middle of the road) and SSP370 (regional rivalry) scenarios in the years 2061–2080 and 2081–2100. In both SSPs, the average future prediction for the period 2061–80 showed an increase in the total suitability area in comparison with the historic period. In conclusion, the study would not only help in eco-restoration of the habitats, but also in recovering the species population and improving its in situ conservation.